Migration and integration : the case for liberalism with borders / Tom Farer. - Farer, Tom J. (Cambridge University Press, 2020)
Migration and Integration clarifies and proposes answers for all of the politically toxic questions associated with large-scale migration from the Global South to the Western liberal democracies. Driven by the conviction that the Alt-Right is using the issues of migration and integration effectively to batter the defenses of liberal democracy, Professor Tom Farer argues that despite its strength, the moral case for open borders should be rejected and that while broadly tolerant of different life styles, the state should enforce core liberal values. Examining closely the policies and practices of various European states, Farer draws on their experience, contrasts it with that of the United States, and provides a detailed strategy for addressing the issues of who should be allowed to enter, how migrant families should be integrated and cultural conflicts resolved. This remarkable elaboration of a liberal position on migration and integration to which moderate conservatives could adhere combines powerful analysis with passionate advocacy.